2004
DOI: 10.1063/1.1756205
|View full text |Cite
|
Sign up to set email alerts
|

Photocurrent in ZnO nanowires grown from Au electrodes

Abstract: Zero-bias anomaly in one-dimensional ultrathin metallic nanowires AIP Advances 2, 032143 (2012) Influence of electron scatterings on thermoelectric effect ZnO nanowires were grown between two Au electrodes on an Al 2 O 3 -deposited Si wafer. Photoresponse, photoresponse spectrum, and current-voltage (I -V) studies were performed for the investigation into photoconduction mechanism in these nanowires. The photoresponse of the nanowires under the continuous illumination of light with above-or below-gap energies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
189
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(197 citation statements)
references
References 11 publications
7
189
0
1
Order By: Relevance
“…Above the band gap energy, the photoconductivity is almost constant (note the semilogarithmic scale) up to the deep UV spectral region, while no photoresponse has been detected in the range from 1.5 to 3.2 eV. The absence of photoconduction upon visible light illumination testifies to the low defect levels, 17,18 such as oxygen vacancies in the ZnO NWs, which is supported by the low intrinsic electron concentration estimated above. The high spectral selectivity combined with high photosensitivity suggest the possibility of using ZnO NWs as "visible-blind" UV photodetectors for commercial, military, and space applications.…”
mentioning
confidence: 66%
“…Above the band gap energy, the photoconductivity is almost constant (note the semilogarithmic scale) up to the deep UV spectral region, while no photoresponse has been detected in the range from 1.5 to 3.2 eV. The absence of photoconduction upon visible light illumination testifies to the low defect levels, 17,18 such as oxygen vacancies in the ZnO NWs, which is supported by the low intrinsic electron concentration estimated above. The high spectral selectivity combined with high photosensitivity suggest the possibility of using ZnO NWs as "visible-blind" UV photodetectors for commercial, military, and space applications.…”
mentioning
confidence: 66%
“…In particular, fabrication of stable and rectifying metal contacts to ZnO remains a challenge despite numerous recent investigations. [1][2][3][4][5][6][7][8][9][10][11][12] A number of studies have addressed various possible fundamental mechanisms affecting Schottky barrier ͑SB͒ performance in ZnO, 1,5,9-13 but none have considered the role of both the surface and subsurface. Thus, while several studies have proposed that surface morphology, hydroxide ͑OH͒, and carbon surface contamination play a dominant role, none have considered the role of subsurface defects and impurities that could alter local carrier concentrations, depletion widths, and tunneling.…”
mentioning
confidence: 99%
“…14-17͒ and ZnO nanostructures [18][19][20][21][22][23] where it was shown that photogenerated holes induce desorption of oxygen absorbed on the surface. Adsorbed oxygen acts as an electron trap and its release enhances the concentration of mobile electrons originating from the native doping and photoexcitation of the ZnO.…”
mentioning
confidence: 99%